Stabilizing Student Engagement in Teaching English at SDIT At-Taqwa Surabaya - Savira Uswatun Hasanah (Education Human and Development Journal, 2022)
Abstract: The COVID-19 pandemic situation that occurred over a long period of time had quite an impact on student learning methods. These emerging learning innovations greatly impact the involvement of students, especially elementary school children. This study aims to identify the relationship between engagement strategies and student's involvement in a hybrid-based English class at SDIT AT-Taqwa Surabaya. This research is a descriptive qualitative study. Data were collected through a process of observation and questionnaires that focused on the types of engagement strategies used, as well as the responses shown by grade 1A and 1B students at SDIT AT-Taqwa Surabaya. The results show that the students' engagement strategies used by grade one English teachers at SDIT AT-Taqwa are varied. These strategies are socio-affective, design, and organization engagement. Teachers strongly emphasize the use of socio-affective engagement strategies, especially in order to increase students' emotional involvement. The teacher understands that to create an active, collaborative and conducive hybrid class, the teacher must build a sense of comfort among the students in the classroom. In other words, the teachers realize that emotional involvement is the foundation in triggering cognitive and behavioral engagement. It can be stated that the hybrid-based English classes at SDIT AT-Taqwa are being conducted successfully and wisely in a very balanced online and offline approach using the available resources.